Bulgarian-Romanian relations in the years 1912–1913 (on the base of Bulgarian, German and Austro-Hungarian diplomatic sources) - Rubacha, Jarosław (Balcanica Posnaniensia. Acta et studia, 2022)
Bulgarian-Romanian relations in the years 1912–1913 (on the base of Bulgarian, German and Austro-Hungarian diplomatic sources). The tensions in Bulgarian-Romanian relations, which had lasted for over thirty years, reached their peak in 1912–1913, and the prospect of Bulgaria breaching the status quo in the Balkans prompted Romania to ask for new security guarantees and territorial compensation. However, the negotiations between Bucharest and Sofia showed significant divergences in the positions of the parties regarding the modification of the Dobruja border, which even the pressure of the great powers could not offset. Therefore, Romania declared war on Bulgaria, but the modification of the border in Dobruja described in the Treaty of Bucharest of 1913 did not restore good relations between neighbouring countries.